Leakage and diffusion simulation of submarine hydrogen-blended natural gas pipeline - Yitao FANG; Haichuan TAN; Liang TANG; Mengjie WANG; Jingfa LI; Yue SU (You-qi chuyun)
Objective Among various safety accidents associated with submarine natural gas pipelines, leakage remains a prevalent concern due to its high frequency. As the transmission of hydrogen-blended natural gas becomes more common through these pipelines, studying the impact of hydrogen blending on the evolution of leakage and diffusion is of utmost importance. Methods Two typical leakage scenarios of submarine hydrogen-blended natural gas pipelines were studied through numerical simulations: anchor break leakage and aperture leakage. The analysis focused on the influence patterns of crucial factors such as hydrogen blending ratios, seawater depths, pipeline burial depths, and sizes of leakage apertures on the leakage and diffusion of these pipelines. Results In both anchor break leakage and aperture leakage scenarios of submarine hydrogen-blended natural gas pipelines, it was observed that seawater velocity influenced the horizontal and vertical diffusion distances of leaking hydrogen-blended natural gas. In the anchor break leakage scenario, the diffusion of leaking hydrogen-blended natural gas in seawater accelerated with a rise in the hydrogen blending ratio. This led to greater horizontal and vertical diffusion distances for leaking hydrogen-blended natural gas compared to pure natural gas within the same leakage duration. Additionally, a direct correlation was noted between the time taken for leaking hydrogen-blended natural gas to reach the sea surface and the pipeline burial depth. Deeper pipeline burial depths led to longer travel times for leaking hydrogen-blended natural gas to reach the sea surface. In the aperture leakage scenarios, the diffusion process of leaking hydrogen-blended natural gas exhibited a deceleration compared to anchor break leakage, primarily attributed to the resistance posed by seabed sediment. Furthermore, an increase in the hydrogen blending ratio also resulted in extended horizontal and vertical diffusion distances of leaking hydrogen-blended natural gas. Notably, a distinct impact on leakage diffusion was identified across varying leakage aperture sizes. Larger leakage apertures allowed leaking hydrogen-blended natural gas to diffuse over greater distances within the same leakage duration. Conclusion The research findings serve as a reference for enhancing the safety of transmission and preventing leakage in submarine hydrogen-blended natural gas pipelines.